1990
DOI: 10.1007/bf01059075
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity and bioaccumulation of 2,5,2?,5?- and 3,4,3?,4?-tetrachlorobiphenyl and Aroclor� 1242 in the amphipodHyalella azteca

Abstract: The addition of 100 micrograms/L of Aroclor 1242 (A1242) or 2,5,2',5'-tetrachlorobiphenyl (TeCB) during 10 week chronic toxicity tests with Hyalella azteca resulted in complete mortality. There were no effects on survival, growth, or reproduction after addition of 30 micrograms/L. Toxic effects were observed at tissue levels of between 30 and 180 micrograms/g on a wet weight basis, and tissue levels appear to be a better indicator of toxicity than levels in water. No toxic effects were observed after additions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
6
31
0
Order By: Relevance
“…There were no effects on growth or reproduction at any concentration which did not also cause significant chronic mortality (Tables 1 to 4). This is consistent with previous observations on the chronic toxicity of cadmium, pentachlorophenol and PCBs to H. azteca (Borgmann et al, 1989b(Borgmann et al, , 1990, but contrasts with the --(~m i a r d et al., 1987). Neither copper nor zinc were completely regulated by the amphipod Echinogammarus pirloti, although zinc accumulation was slow, suggesting some attempt at regulation (Rainbow & White, 1989).…”
Section: Pb CD Hg Cu Znsupporting
confidence: 83%
“…There were no effects on growth or reproduction at any concentration which did not also cause significant chronic mortality (Tables 1 to 4). This is consistent with previous observations on the chronic toxicity of cadmium, pentachlorophenol and PCBs to H. azteca (Borgmann et al, 1989b(Borgmann et al, , 1990, but contrasts with the --(~m i a r d et al., 1987). Neither copper nor zinc were completely regulated by the amphipod Echinogammarus pirloti, although zinc accumulation was slow, suggesting some attempt at regulation (Rainbow & White, 1989).…”
Section: Pb CD Hg Cu Znsupporting
confidence: 83%
“…Borgmann et al [4] found that 2,2Ј,5,5Ј-tetrachlorobiphenyl (TeCB) bioaccumulates from water into the amphipod Hyalella azteca linearly up to 100 g/L and then levels off. Borgmann et al [4] found that 2,2Ј,5,5Ј-tetrachlorobiphenyl (TeCB) bioaccumulates from water into the amphipod Hyalella azteca linearly up to 100 g/L and then levels off.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the most important aspect of SARs is the degree of ortho-substituted chlorination [10,11]. Borgmann et al [4] proposed that this structureactivity relationship for H. azteca did not fit the vertebrate model because the mechanism of toxicity in vertebrates is associated with arylhydrocarbon hydroxylase (AHH) induction and AHH activity is much lower in this aquatic invertebrate than in vertebrates. However, a non-ortho-substituted TeCB was found to be no more toxic than an ortho-substituted TeCB in the amphipod H. azteca [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hyalella azteca is a sentinel organism that is widely used in ecotoxicology laboratories for the asssessment of chemical risk to aquatic environments because of the many advantages it offers, such as the widespread distribution and common occurrence in association with freshwater environments, together with its ecological importance, ease of culturing and handling during testing, rapid growth, short life cycle, sensitivity to diverse xenobiotics in water. H. azteca has been used in water-only acute and sublethal toxicity tests with various chemicals (FDA 1987;Borgmann et al 1989Borgmann et al , 1990Borgmann et al , 1991Borgmann et al , 2005Borgmann et al , 2007Schubauer-Berigan et al 1993;Phipps et al 1995). Biological endpoints for these tests have included survival, growth, and reproductive success in partial or full life-cycle studies (ISO 2011).…”
Section: Introductionmentioning
confidence: 99%